Clinical application of digital technology in the reconstruction of soft tissue defects of the lower extremity with free superficial circumflex iliac artery flap - Li, Jiayu; Luo, Xuchao; Liu, Anming; Zou, Yonggen (Frontiers in Surgery, 2022)
Objective This paper aims to investigate the feasibility and clinical effectiveness of digital technology in the clinical application of free superficial circumflex iliac artery flap (SCIP) for repairing soft-tissue defects in the lower extremities. Methods From January 2020 to December 2021, 16 patients with lower extremity soft tissue defects requiring flap repair were selected, and preoperative 3D digital reconstruction of the abdominal donor area and lower extremity recipient area were performed using digital technology combined with highly selective abdominal computed tomography angiography, and virtual design and flap cutting were performed using the software self-contained tool. During the actual surgery, the intraoperative design and excision of the superficial iliac circumflex artery were guided by the preoperative digital design, and the donor sites of the flap were closed directly. Results In all cases, digital models of the donor area of the abdominal SCIP were successfully established, which could clearly showed the distribution, course, and diameter of the main trunk and the perforators and other relevant anatomical information and successfully guided the design and excision of the flap during surgery. All flaps successfully survived after surgery, and both the flap recipient and donor sites healed in one stage. All patients were followed up for 2–12 months on average (mean 8.6 months), and the flaps were not bulky and had a satisfactory appearance, with no significant difference in color compared with the surrounding skin and a little pigmentation around the flap. Only linear scarring was left in the donor areas, and there was no restriction of hip movement. Conclusion This study used digital technology combined with a SCIP to repair lower extremity soft-tissue defects. The preoperative three-dimensional reconstruction of the digital model of the flap optimally designed the surgical plan, reduced the surgical risk and difficulty, shortened the surgical time, and had some significance for clinical precision, safety, and personalized design of the abdominal flap.